Endovascular therapy and medical management of large-core infarcts: prognostic determinants in a retrospective cohort - Yi Li; Yi Li; Hao Tao; Hao Tao; Huan Liu; Huan Liu; Xiang Fan; Xiang Fan; Meng-Yu Zhong; Meng-Yu Zhong; Jie Huang; Neng-Wei Yu; et al. (Frontiers in Neurology)
IntroductionTo investigate the independent prognostic risk factors in acute ischemic stroke patients with large-core infarcts, including patients beyond standard eligibility thresholds for core volume or ASPECTS and provide evidence for early clinical intervention.MethodsThis retrospective cohort study analyzed the clinical data of 96 consecutive patients with large-core infarcts admitted to a regional stroke center between June 2020 and June 2024. Participants were stratified into poor outcome [modified Rankin Scale (mRS) 4–6] and favorable outcome (mRS 0–3) groups based on the 90-day post-intervention assessments. Comparative analyses of the baseline demographics, biochemical parameters, neuroimaging metrics, and treatment modalities were conducted. Univariate analysis followed by multivariate logistic regression was used to identify independent predictors of favorable outcome. A prespecified EVT subgroup analysis was performed, including procedural variables (onset-to-puncture time, puncture-to-recanalization time) and clinical variables in multivariate regression.ResultsAmong the 96 patients, 17 (17.7%) achieved favorable outcomes (mRS 0–3) and 79 (82.3%) had poor outcomes (mRS 4–6). Multivariable analysis identified four independent predictors of poor outcome: non-receipt of EVT [OR = 10.22, 95% confidence interval (CI): 1.05–99.76], hyperglycemia (per 1 mmol/L; OR = 1.76, 95% CI: 1.10–2.82), and higher platelet count (per 103/μL; OR = 1.02, 95% CI: 1.00–1.03) (all p < 0.05). In the EVT subgroup (n = 62), hyperglycemia remained significantly associated with poor outcomes (OR = 1.70, 95% CI: 1.04–2.78, p = 0.034).ConclusionEVT significantly improves functional outcomes in large-core infarcts. Preoperative hyperglycemia and elevated platelet count are independent predictors of poor outcomes. These findings support standardized protocols that integrate early EVT with glycemic control and coagulation monitoring in this patient population.